Polymorphisms of the angiotensin-converting enzyme and angiotensinogen gene in patients with atrial fibrillation - FAK, ALİ SERDAR; ÖZBEN SADIÇ, BESTE; YEŞİLDAĞ, OSMAN (SAGE PUBLICATIONS LTD, 2011)
Activation of the renin-angiotensin system (RAS) is associated with atrial fibrillation (AF). The aim of this study was to investigate the relation between AF and polymorphisms in RAS. One hundred and fifty patients with AF, 100 patients with no documented episode of AF and 100 healthy subjects were consecutively recruited into the study. The angiotensin-converting enzyme (ACE) insertion/deletion (I/D) polymorphism, and the M235T, A-20C, and G-6A polymorphisms of the angiotensinogen gene were genotyped. Patients with AF had significantly lower frequency of II genotype of ACE I/D and higher frequency of angiotensinogen M235T polymorphism T allele and TT genotype and G-6A polymorphism G allele and GG genotype compared with the controls. AF patients had significantly larger left atrium, higher left ventricular mass index (LVMI) and higher frequency of significant valvular pathology. ACE I/D polymorphism II genotype, angiotensinogen M235T polymorphism TT genotype and G allele and GG genotype of angiotensinogen G-6A polymorphism were still independently associated with AF when adjusted for left atrium, LVMI and presence of significant valvular pathology. Genetic predisposition might be underlying the prevalence of acquired AF. Patients with a specific genetic variation in the RAS genes may be more liable to develop AF.
Keywords: Angiotensin-converting enzyme; angiotensinogen; atrial fibrillation; genetic susceptibility; polymorphism; renin-angiotensin system; INSERTION DELETION POLYMORPHISM; LEFT-VENTRICULAR HYPERTROPHY; II TYPE-1 RECEPTOR; ESSENTIAL-HYPERTENSION; MYOCARDIAL-INFARCTION; HEART-FAILURE; RISK-FACTORS; POPULATION; LONE; CARDIOMYOPATHY